The One Divine Nature - Hasker, William (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2019)
The doctrine of the Trinity affirms that there are three divine Persons, each of whom is fully God, who have between them a single concrete divine nature. This paper attempts two show that, and how, these claims are coherent rather than contradictory. In the process a model for the Trinity is proposed using the notion of constitution.